Analisis Sikap dan Bakat Mahasiswa Program Studi Pendidikan Ekonomi UNP terhadap Profesi Guru dan Pengaruhnya pada Prestasi Belajar - Rino, Rino (Fakultas Ilmu Sosial Universitas Negeri Padang, 2011)
ABSTRACT The objective of this study is to analyze the attitudes and talents of students towards teacher profession and their impact on their academic result. The sample of this study was 78 students Economics Education Studies Program in Economy Faculty, The State University of Padang. The data were analyzed with descriptive and multiple regression. The finding of this study indicated that students showed positive attitudes and talents toward teacher profession. Besides, the attitudes and talents had positive effect towards their academic achievement Kata Kunci: Sikap, Bakat, Prestasi Belajar